2014
DOI: 10.1007/s10103-014-1659-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effects of ultrasound and laser on the pain relief in women with hand osteoarthritis

Abstract: Patients with pain avoid movements, leading to a gradual impairment of their physical condition and functionality. In this context, the use of ultrasound (US) and low-level laser therapy (LLLT) show promising results for nonpharmacological and noninvasive treatment. The aim of this study was evaluated the synergistic effects of the US and the LLLT (new prototype) with or without therapeutic exercises (TE) on pain and grip strength in women with hand osteoarthritis. Forty-five women with hand osteoarthritis, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 45 publications
3
20
0
1
Order By: Relevance
“…In addition to such signi icance, there was a return to the activity of playing the piano, without any sign of pain or limitation. In this way, our results corroborate the results of singular treatments found in the literature [7,8]. However, the results obtained make this model of equipment and therapy potentially used more bene icial for the treatment of osteoarthritis.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to such signi icance, there was a return to the activity of playing the piano, without any sign of pain or limitation. In this way, our results corroborate the results of singular treatments found in the literature [7,8]. However, the results obtained make this model of equipment and therapy potentially used more bene icial for the treatment of osteoarthritis.…”
Section: Resultssupporting
confidence: 91%
“…The Auscan questionnaire presented a signi icant decrease for pain quanti ication of -233.33% (Table 1). These results are corroborated by recent studies published by our group, which points out a great improvement in pain questionnaires for knee and hand osteoarthritis [7,8]. In addition to such signi icance, there was a return to the activity of playing the piano, without any sign of pain or limitation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are in line with Paolillo et al who combined LLLT with ultrasound. The present results are also reconcilable with Brosseau et al who admittedly found only few significant differences between sham and active LLLT patients, yet demonstrated improvement over time in both groups with a general tendency for greater changes in the main outcome measures, such as pain, morning stiffness, grip strength, and functional status, in the active LLLT group.…”
Section: Discussionsupporting
confidence: 93%
“…26 We choose an infrared wavelength, because the penetration is deeper if compared with the red wavelength used in in vitro studies. In addition, we used a greater power and fluence, if compared with in vitro studies, but smaller values compared with clinical trials, 27,28 because human skin levels, skin color, and body composition (fat, muscle, and bone) may create a biological barrier for the phototherapy, suggesting the use of a greater power and fluence in treatment protocols, in contrast to what is used in animals. The principle of the Arndt-Schultz law states that very low doses of radiation can cause a strong physiological response.…”
Section: Lllt Exercise and Muscle Recovery 189 Discussionmentioning
confidence: 99%